Unhiding Colombian orchid treasures II: Lepanthes leonmoralesii (Orchidaceae), a new species from the Norte de Santander and Santander departments - Restrepo, Eugenio; Joya, Diana P.; Arango-Carvajal, Susana M.; Caro-Ayala, Heidy C.; Morales-Morales, Paula A.; Suescún, Diego (Phytotaxa, 2026)
A new species of Lepanthes from the northeastern Andes of Colombia, occurring in the departments of Norte de Santander and Santander, is described and illustrated. The new species is similar to L. climax, but differs in having sublax and abruptly decurved coflorescences, a well-developed oblong lower lobe of the petals, and considerably larger, microscopically pubescent lip blades, obtusely ovate and falcate. A distribution map is provided, together with notes on habitat and ecology, and a preliminary assessment of its extinction risk. Given its restricted distribution and the current condition of its habitat, the species is assessed as Endangered (EN) under the criteria of the International Union for the Conservation of Nature (IUCN).